Videos with groundwater in Svalbard ... - Sinitsyn, Anatoly (Zenodo, 2023)
S1.a2-1. Drilling through small, cracked "mound" icing at Longyearelva behind Elvesletta Nord (18.04.2017, location a2 in Table 1). Video: © Anatoly Sinitsyn. Video S1.a2-2. Water at artesian pressure, which appeared on the surface of icing at Longyearelva behind Elvesletta Nord (18.04.2017, location a2 in Table 1). Video: © Anatoly Sinitsyn. Video S1.a5. Large "flat and spread" not cracked icing at Elvesletta (18.04.2017, location a5 in Table 1). Photo: © Anatoly Sinitsyn. Video S1.a6. Medium, mostly "flat and spread" not cracked and cracked icings at Longyearelva above old bridge over the Road 503 (03.05.2017, location a6 in Table 1). Video: © Anatoly Sinitsyn. Video S1.a8. Small, not cracked icings at Longyearelva between Nybyen and Sverdrupbyen (03.05.2017, location a8 in Table 1). Photo: © Anatoly Sinitsyn. Video S1.a16: spring with artesian pressure on the slope about the Roar 300 (09.09.2023, location a16 in Table 1). Video: © Anatoly Sinitsyn/Sintef. Video S1.j. Spring at the foot of the Hovtinden ...